The small finds from Tell el-Ghaba (North Sinai, Egypt): A review - Calomino, Eva Amanda (Antiguo Oriente, 2021)
The Small Finds from Tell el-Ghaba (North Sinai, Egypt): A Review This work proposes a review and characterization of the small finds from Tell El-Ghaba archaeological site (North Sinai, Egypt), an urban settlement that was occupied between the beginning of the Third Intermediate Period and the early Saite period (10th-7th centuries BC). These objects were recovered in the systematic excavations carried out by the Argentine Archaeological Mission between 1995 and 2010. First, the concept of “small finds” and the inherent difficulties that complicate the approach to these assemblages are problematized, considering they require new proposals; second, a systematized review of the objects cataloged as small finds in the site is carried out. Finally, from a new analytical proposal, a selected sample of special findings is characterized, considering both published data and databases; these objects were classified in categories and subcategories without using function as the primary classification value. From this, the main characteristics of these objects are exposed, and the first steps are taken to interpret the small finds from Tell el-Ghaba. In turn, this general characterization allows, on the one hand, to deal with a large database; on the other hand, to achieve a global approach parallel to an individual approach, according to the characteristics of published catalogs.